Race-time prediction for the Va`a paralympic sprint canoe - Hudson, D. A.; Crossley, H. C.; Taunton, D. J.; Blake, J. I. R. (Procedia Engineering, 2014)
The 2016 Paralympic Games in Rio de Janeiro will see 200m sprint canoe events for the first time, using the Va`a class. The aim of this study is to predict race times for the Va`a over a 200m sprint event, through simulation of the hydrodynamic resistance of the hull (with outrigger) and the propulsion provided by the athlete. Such a simulation, once suitably validated, allows investigation of design and configuration changes on predicted race performance. The accuracy of the simulation is discussed through a comparison to times recorded for an athlete over a 200m race distance.